Aplicação de espectroscopia raman e análise multivariada na caracterização e monitoramento in situ da síntese de cocristais de carbamazepina-nicotinamida e ibuprofenonicotinamida - Soares, Frederico Luis Felipe (2014)
In this work, the PAT tools were used (Raman spectroscopy with an in situ analyzer and multivariate tools) to proceed a crystallization monitoring and quantification of cocrystals of carbamazepine nicotinamide (CBZ NCT) and ibuprofen nicotinamide (IBP NCT). At first, it was performed the cocrystals syntheses that would be used as standard cocrystal during the course of this work, employing a method described in the literature. These crystals were characterized by differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), mid-infrared (MIR) and Raman spectroscopy. After the confirmation of the crystalline structure by the solid state analytical techniques, these crystals were used on a mixture design with three components (cocrystal, coformer A and coformer B) to develop an analytical curve employed in the quantification of the cocrystals. It was evaluated with the solid state analytical technique and quantification chemometrics methods, such as the PLS, which enabled a better cocrystal quantification among its coformers. Raman spectroscopy was the technique that presented the lowest error values, both in calibration and validation stages, with square mean errors of prediction ranging from 1.5 4.5 % for each analyte. For cocrystal synthesis and monitoring, it was used as a crystallization reaction procedure. Thus, it was prepared using a nicotinamide solution in water with a concentration near saturation level. This solution was added to the coformer, in solid state. The reactions were performed at different temperatures and monitored by the Raman spectroscopy. For both cocrystals, it was possible to observe a crystallization with a high yield from 60 °C, being the fact unpublished by the literature, since most of the cocrystallization reactions use organic solvents. The employment of multivariate curve resolution (MCR-ALS) enabled to observe distinctly the main points of the reaction, such as drugs dissolution, crystal nucleation and cocrystal crystallization, which can be easily employed on a routine procedure in the pharmaceutical industry.